Evaluation of health applications to support the asthma treatment process, available in Poland - Wilczek, Arkadiusz; Woźniczka, Patrycja; Rogalska, Anna (Journal of Education, Health and Sport, 2023)
Introduction: Asthma is one of the most frequently diagnosed chronic diseases in the world. All elements of treatment should primarily focus on controlling the disease and activating the patient and his participation in the treatment process. With the help of e-health and telemedicine in the form of applications for smartphones, thus independent coping with chronic diseases. The aim of the study was a quantitative and qualitative assessment of applications supporting such a business process in Polish. Material and methods: The study was based on a review and checking of applications using criteria using various types of mobile devices, algorithms by various operating systems. The search for those qualified for the analysis was carried out from October 14 to November 8, 2022 on the basis of the words: asthma, application, dairy products. Results: 4 asthma apps were analyzed. The highest quality documents of the Mytherapy application - 5.5 points/12 points - do not verify this threshold of good quality applications - a minimum of 75% of use to obtain points. Conclusions have been checked: These conclusions suggest a direction, regardless of the attempt to create an application that addresses the topic holistically, as well as research in this area.